The translation and adaptation of Alice's Adventures in Wonderland into isiNdebele. Issue 2 (6th September 2019) - Nkomo, Dion
Abstract: This article reflects on the translation of Lewis Carroll's Alice's Adventures in Wonderland into the isiNdebele language of Zimbabwe. The isiNdebele translation, Insumansumane zika-Alice, is one of the numerous translations produced towards the 150th commemorative exhibition of Carroll's legacy following the publication of Wonderland in 1865. The translations resulted in Wonderland becoming one of the most translated English novels, thereby vindicating the 'universal-child hypothesis' propounded by Warren Weaver in an earlier appraisal of Wonderland translations fifty years earlier. Weaver regarded the translation of Wonderland as a measure of the popularity of the text among children, who are arguably fascinated by Alice, with whom they are assumed to identify. This article problematises this argument in the light of most translations being initiated by non-mother-tongue speakers of target languages. It is argued that Alice's worldwide appeal should not be taken for granted as a universal one, partly because of her particular identity, which is different from the diverse target readers. Therefore, the question of whether Alice can really become African reflects on the domestication approach that was adopted by the isiNdebele translator, among others. Special attention is paid to proper nouns and other complex features characterising Carroll's language usage.